Nerve Stimulator versus Ultrasound-Guided Femoral Nerve Block; a Randomized Clinical Trial - Forouzan, Arash; Masoumi, Kambiz; Motamed, Hasan; Gousheh, Mohammad Reza; Rohani, Akram (Archives of Academic Emergency Medicine, 2017)
Introduction: Pain control is the most important issue in emergency department management of patients with femoral bone fractures. The present study aimed to compare the procedural features of ultrasonography and nerve stimulator guided femoral nerve block in this regard. Method: In this randomized clinical trial, patients with proximal femoral fractures presenting to emergency department were randomly divided into two groups of ultrasonography or nerve stimulator guided femoral block and compared regarding success rate, procedural time, block time, and need for rescue doses of morphine sulfate, using SPSS 20. Results: 50 patients were randomly divided into two groups of 25 (60% male). The mean age of studied patients was 35.14 ± 12.95 years (19 – 69). The two groups were similar regarding age (p= 0.788), sex (p = 0.564), and initial pain severity (p = 0.513). In 2 cases of nerve stimulator guided block, loss of pinprick sensation did not happen within 30 minutes of injection (success rate: 92%; p = 0.490). Ultrasonography guided nerve block cases had significantly lower procedural time (8.06 ± 1.92 vs 13.60 ± 4.56 minutes; p < 0.001) and lower need for rescue doses of opioid (2.68 ± 0.74 vs 5.28 ± 1.88 minutes; p < 0.001). Conclusion: Ultrasonography and nerve stimulator guided femoral block had the same success rate and block duration. However, the ultrasonography guided group had lower procedure time and lower need for rescue doses of morphine sulfate. Therefore, ultrasonography guided femoral block could be considered as an available, safe, rapid, and efficient method for pain management of femoral fracture in emergency department.